Innovating language curriculum design through design thinking: A case study of a blended learning course at a Colombian university. (November 2020) - Crites, Kelley; Rye, Emma
Abstract: This paper reports on the outcome of an exploratory case study based on the implementation of Design Thinking (DT) in a Language Curriculum Design (LCD) process during a top-down program reform at a university in Colombia. DT was implemented in response to the challenge of designing an original curriculum with few resources at hand and very little time. It was found that by integrating DT into LCD, the design process became more collaborative, creative and efficient. It also improved teachers' experiences both in the design process and when teaching the course. Ultimately, by implementing DT from the initial stages of the design process, future iterations of the course were instilled with the philosophy of DT leading to more consistent curriculum evaluation and development. This paper concludes with a discussion on how this approach could potentially be applied to multiple educational contexts in order to improve curriculum design and other processes. It is also suggested that DT could be an approach used during future language policy reform in Latin America, particularly in the context of social innovation.